Cooperatives as The Pillars of The Pancasila Economic Driving Force - Riza Yonisa Kurniawan; Agung Haryono (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2023)
This article describes the economic concept of Pancasila based on strategic values based on five principles developed by the founders of the country. The Indonesian economy is still an established capitalist economic system and has not yet been able to rise. During the reform period, the head of state has not been able to fully represent a humane, prosperous, and socially just economy. The economic life of the Indonesian people is still colored by policies of deregulation, privatization, and trade liberalization which are detrimental to the interests of the Indonesian people. The research method uses library research. This study shows that the Pancasila economy has the spirit of divinity, humanity, national unity, democracy, and social justice. The conclusion of this study is that the Pancasila economy exists in the form of cooperatives as the main pillar that aims to achieve the welfare of the Indonesian people.